Chronology of settlements with pre-Incan and Incan occupations superimposed. The case of Pucará de Tilcara (Humahuaca gorge, Argentina) - Greco Mainero, Mariano Catriel (2015)
The region of central and South Andes was, ca. 9th and 15th AD, the stage of development of political systems tending to demographic centralization in villages with defensive structures, known as Pucará. The chronological accuracy for these phenomena still remains with uncertainties mainly because this involves spaces of long and superimposed occupations, masked by the Incan domination. Thus, this article analyzes the history of the occupation at Pucará de Tilcara, one of the biggest populated centers of the Humahuaca gorge (Quebrada de Humahuaca, Argentine). 25 radiocarbon dates are critically evaluated to judge its reliability. Bayesian statistics shows that all the dated spaces were used in a long term basis. The most ancient signs are in the middens and relate at least to the 10th century AD, and the occupation of the housing areas could be calculated to the 13th and 16th centuries. A moment of higher intensity of occupation is observed during the Incan time. This redefinition of this site occupation shows the need to statistically analyze the dates in order to differentiate the moments of occupation.